Solar Magnetic Polarity Effect on Neutron Monitor Count Rates: Comparing Latitude Surveys and Antarctic Stations ... : تأثير القطبية المغناطيسية الشمسية على معدلات عدد مراقبي النيوترونات: مقارنة استطلاعات خطوط العرض ومحطات أنتاركتيكا ... - K. Poopakun; Waraporn Nuntiyakul; Sidarat Khamphakdee; Achara Seripienlert; D. Ruffolo; P. A. Evenson; Peng Jiang; Pongpichit Chuanraksasat; K. Munakata; M. L. Duldig; J. E. Humble; J. Madsen; et al. (OpenAlex, 2023)
Abstract The Galactic cosmic-ray spectrum manifests pronounced variations over the 11 yr sunspot cycle and more subtle variations over the 22 yr solar magnetic cycle. An important tool to study these variations is repeated latitude surveys with neutron monitors (NMs) on board icebreakers in conjunction with land-based references. We revisit 13 annual latitude surveys from 1994 to 2007 using reference data from the Mawson NM instead of McMurdo NM (which closed in 2017). We then consider two more latitude surveys (2018 and 2019) with a monitor similar to the 3NM64 in the previous surveys but without lead rings around the central tube, a so-called "semi-leaded neutron monitor." The new surveys extend the linear relationship among data taken at different cutoff rigidity ranges. They also confirm the "crossover" measured near solar minima during epochs of opposite solar magnetic polarity and the absence of a crossover for epochs having the same solar magnetic polarity. ... : يُظهر طيف الأشعة الكونية المجرية اختلافات واضحة خلال دورة البقع الشمسية لمدة 11 عامًا واختلافات أكثر دقة خلال الدورة المغناطيسية الشمسية لمدة 22 عامًا. ومن الأدوات المهمة لدراسة هذه الاختلافات عمليات مسح خطوط العرض المتكررة باستخدام أجهزة مراقبة النيوترونات (NMs) على متن كاسحات الجليد بالتزامن مع المراجع الأرضية. نعيد النظر في 13 دراسة استقصائية سنوية لخطوط العرض من عام 1994 إلى عام 2007 باستخدام بيانات مرجعية من Mawson NM بدلاً من McMurdo NM (التي أغلقت في عام 2017). ثم ننظر في مسحين آخرين لخطوط العرض (2018 و 2019) مع شاشة مماثلة لـ 3NM64 في المسوحات السابقة ولكن بدون حلقات رصاص حول الأنبوب المركزي، وهو ما يسمى "شاشة النيوترون شبه الرصاصية." توسع الاستطلاعات الجديدة العلاقة الخطية بين البيانات المأخوذة في نطاقات صلابة القطع المختلفة. كما يؤكدون "التقاطع" الذي تم قياسه بالقرب من الحدود الدنيا للطاقة الشمسية خلال عصور القطبية المغناطيسية الشمسية المعاكسة وغياب التقاطع للعصور التي لها نفس القطبية المغناطيسية الشمسية. ...